Efektivitas Penggunaan Buku Al Arabiyah Baina Yadaik dalam Kemahiran Berbicara di Universitas Al Azhar Indonesia - Auliya Arden; Febri Priyoyudanto (Morfologi : Jurnal Ilmu Pendidikan, Bahasa, Sastra dan Budaya, 2025)
The book Al Arabiyah Baina Yadaik is a guide book for learning Arabic which includes four skills in Arabic, namely speaking skills, listening skills, reading skills and writing skills. In this book there are many important aspects to improve students' speaking skills. The method used in this research is descriptive qualitative. This method was chosen to be able to describe real phenomena without any engineering involved. The data source in this research is Arabic Language and Culture students at Al Azhar University Indonesia. The problem discussed in this research is measuring the effectiveness of the book Al Arabiyah Baina Yadaik in speaking proficiency. The aim of this research is to see the effectiveness of using the Al Arabiyah Baina Yadaik book in speaking proficiency. The results of this research are related to the components of book content, the role of the teacher, and the role of students in speaking proficiency in the Arabic language learning process.